Double Role: Cracking the Code of the Sandwich Generation in “Home Sweet Loan” Movie - Drs. Saifudin Zuhri; Alicia Putri Raja Dima (Lavish Opulent Education, 2025)
This study examines how the film Home Sweet Loan represents the phenomenon of the sandwich generation using John Fiske’s semiotic approach. The term “sandwich generation” refers to individuals who bear financial responsibility for two generations simultaneously—their parents and their siblings or children. This research adopts a descriptive qualitative method, analyzing the film through three levels of codes: reality, representation, and ideology. The findings reveal that, at the reality level, the film highlights Kaluna’s daily life as the family’s main provider: working, managing household chores, and supporting the financial needs of other family members. At the representation level, the film employs cinematographic elements, dialogue, and narrative to illustrate Kaluna’s dilemma in balancing her personal aspirations with family obligations. Meanwhile, at the ideological level, the film conveys moral values such as sacrifice, sincerity, solidarity, and the cultural and social pressures that reinforce the position of the sandwich generation within society. This research demonstrates that film as a mass medium serves not only as entertainment but also as a form of social reflection that can shape public perspectives on the sandwich generation issue. Theoretically, this study contributes to the application of semiotic theory in communication studies. Practically, it is expected to help the public and creative industry practitioners better understand the realities and challenges faced by the sandwich generation and highlight the importance of presenting more sensitive and empathetic representations in films Keywords: sandwich generation, Home Sweet Loan, John Fiske’s semiotics, representation, moral values.